2007
DOI: 10.1007/bf03347428
|View full text |Cite
|
Sign up to set email alerts
|

Corticotroph axis sensitivity after exercise: Comparison between elite athletes and sedentary subjects

Abstract: Strenuous exercise activates the hypothalamic-pituitary-adrenal (HPA) axis. Several reports showed that physical training is associated with a decreased efficiency of the feedback control of HPA axis. The aims of the present study were: 1) to evaluate the differences in the mechanical, hormonal, and lactate responses to a high-intensity isokinetic exercise among different groups of competitive athletes (CA, no.=20) of power and endurance disciplines and sedentary controls (SED, no.=10); 2) to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 23 publications
4
47
2
2
Order By: Relevance
“…It is well known that physical and mental stress elicit the release of cortisol from HPA axis, by which stress can modulate various immune responses 33) . Exercise in the present study could cause comparable increases in saliva cortisol levels to those observed in previous studies 34,35) . Cortisol is important hormone in the regulation of intermediate metabolism and stress.…”
Section: ⅳ.Discussionsupporting
confidence: 89%
“…It is well known that physical and mental stress elicit the release of cortisol from HPA axis, by which stress can modulate various immune responses 33) . Exercise in the present study could cause comparable increases in saliva cortisol levels to those observed in previous studies 34,35) . Cortisol is important hormone in the regulation of intermediate metabolism and stress.…”
Section: ⅳ.Discussionsupporting
confidence: 89%
“…A hypothesis based on the presence of GRE in MASP2 promoter and the antiinflammatory response of glucocorticoids in general is that in control subjects exercise induces cortisol secretion that inhibits MASP2 transcription through GRE, whereas at least in a subgroup of CFS subjects, exercise-induced cortisol secretion is below a threshold (hypocortisolism) required to inhibit MASP2 expression. Although cortisol was not measured in this study, other studies have reported significant increases in cortisol and its correlation with postexercise performance in healthy subjects (50)(51)(52)(53). Accumulating evidence suggests that physical exercise, depending on the kind of exercise and subject characteristics, can act as a powerful modulator of the HPA axis and influence central nervous system functions in general (54,55).…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, the need for both nuclear FOXO1 and activated GR to fully activate MuRF1 may be protective and prevent unnecessary muscle breakdown. For example, following intense exhaustive exercise, circulating cortisol levels increase (6,31), yet elevated cortisol is generally not associated with an increase in the breakdown of contractile proteins, nor is loss of muscle mass a consequence of endurance training (33). Thus, the need for additional factors to fully activate MuRF1 gene expression could protect the muscle from breakdown under certain physiological conditions.…”
Section: Discussionmentioning
confidence: 99%